2019
DOI: 10.3390/jimaging5070065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Relative Humidity on Wood Sample: A Climate Chamber Experimental Simulation Monitored by Digital Holographic Speckle Pattern Interferometry

Abstract: Relative humidity (RH) changes are a natural environmental effect that forces organic materials to a constant cycle of achieving equilibrium. The present work is part of an ongoing research based on the hypothesis that the inevitable deleterious effects of the RH natural cycle may be prevented or minimized if a deformation threshold is assigned to each monitored endangered object prior to exposure to structural damage. In this paper the characterization of the behavior of a softwood sample (1.0 cm thick) submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, several other biological systems can use wood as a supportive substrate where nutrient molecules (carbohydrates and proteins) can easily be found. Although different degradation steps can be distinguished in relation to woody plant species and preservation strategies, a relevant role is played by temperature, relative humidity, and lighting, particularly in indoor environments, such as museums, libraries, and archives [8][9][10][11][12][13][14][15]. Environmental conditions are closely related to microbial colonization and insect infestation.…”
Section: Microbial Taxa Identificationmentioning
confidence: 99%
“…Moreover, several other biological systems can use wood as a supportive substrate where nutrient molecules (carbohydrates and proteins) can easily be found. Although different degradation steps can be distinguished in relation to woody plant species and preservation strategies, a relevant role is played by temperature, relative humidity, and lighting, particularly in indoor environments, such as museums, libraries, and archives [8][9][10][11][12][13][14][15]. Environmental conditions are closely related to microbial colonization and insect infestation.…”
Section: Microbial Taxa Identificationmentioning
confidence: 99%
“…Over previous study [14], it was experimentally shown that the rate of RH changes is an important factor for the reaction of materials and that there is a large difference of impact of RH change depending on the object nature: organic or inorganic. In more recent experimental research of Tornari et al with holographic interferometry was experimentally shown that the on line real time potential of the technique to differentiate the RH impact on different materials and composites is very promising for material research in Museum environment [14][15][16], Tornari and al examined wood species samples hardwood and softwood with recent representative materials being pine (Pinus sylvestris) and oak (Quercus ssp) in different cuts. The shrinkage percentage of Pinus sylvestris for radial cut is 5.2% for tangential cut is 8.3% and the ratio tangential/radial 1.6, respectively [17].…”
Section: Wood Species and Its Relationship With The Environmentmentioning
confidence: 99%
“…The experiments were carried out in a homemade airtight climate chamber at FORTH and the aim was to evaluate the deformation of the surface under museum-like RH fluctuations. The DHSPI system has been developed by FORTH [1,6,7,25]. The optical path of the system is based on off-axis transmission holography in the double exposure phase-shifted holographic interferometry mode of application.…”
Section: Experimental Parametersmentioning
confidence: 99%